(-w+6)-(-9w+10)=

Simple and best practice solution for (-w+6)-(-9w+10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-w+6)-(-9w+10)= equation:


Simplifying
(-1w + 6) + -1(-9w + 10) = 0

Reorder the terms:
(6 + -1w) + -1(-9w + 10) = 0

Remove parenthesis around (6 + -1w)
6 + -1w + -1(-9w + 10) = 0

Reorder the terms:
6 + -1w + -1(10 + -9w) = 0
6 + -1w + (10 * -1 + -9w * -1) = 0
6 + -1w + (-10 + 9w) = 0

Reorder the terms:
6 + -10 + -1w + 9w = 0

Combine like terms: 6 + -10 = -4
-4 + -1w + 9w = 0

Combine like terms: -1w + 9w = 8w
-4 + 8w = 0

Solving
-4 + 8w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 8w = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 8w = 0 + 4
8w = 0 + 4

Combine like terms: 0 + 4 = 4
8w = 4

Divide each side by '8'.
w = 0.5

Simplifying
w = 0.5

See similar equations:

| -120=-13x-7x | | 5(y+5)-8y=-2 | | -2(d-2)+4=-12 | | 3*3+x=x*3-2 | | 7c-6=15 | | 8.5x-2(2x+8)= | | 12a-10a-a+2=10 | | 15r+9=60 | | 15d-8d-7=7 | | 3*3+x=2*3-2x | | -4b+-5b=9 | | 3n+6n+-10n+-13=-5 | | -11c=-11 | | 2(q-5)+2=16 | | (3x-5)-(6x-1)= | | X=2.25+.75y | | x^2+8x=3x+24 | | 13s+16s-20s=36 | | 8x^5=2x^2m+3 | | -8u+30=-2u | | 8(f-87)-6=66 | | -9(1/2x-3) | | 79g-73g=54 | | 9(t+1)-13=14 | | (X-4)+3(x+5)=51 | | 4(q-13)-6=2 | | -5v-17=9(v-5) | | p*204=342 | | -3/5*-3/5*-3/5*-3/5*-3/5 | | 10-d=4 | | 12b+3b-6b-8b-1=15 | | 7log(3x)+3log(5x)=5 |

Equations solver categories